Capital Structure and Commercial Banks Performance in Nigeria - Akindele Jamiu, Adeniyi; Asri, Marsidi; Adedeji Samuel, Babatunji (Human Resource Management Academic Research Society, 2020)
Decision relating to capital structure is of great important to an organization as capital performs several indispensable functions in the operations of banks, among which are to mitigate against risk and fragility, maintenance of public confidence as well as enhancing deposits mobilization and efficiency. It is imperative for managers to choose an appropriate financing mix which is a key decision for the growth and going concern of any financial institutions. This study used profit after tax and earnings per share as a measure of performance and employed panel regression technique to analyse data collected from a sample of fourteen quoted commercial banks between 2009 to 2016. The result shows a significant relationship between debt and profitability of commercial banks in Nigeria. The study concludes that debt can be significantly influenced by liquidity and shareholders’ wealth. Consequently, the study recommend that commercial bank managers should not depend on debt capital as a source of financing the organization capital structure but rather use retained earnings of the business and consider debt as the least alternatives